Upregulation of interleukin-33 and thymic stromal lymphopoietin levels in the lungs of idiopathic pulmonary fibrosis. Issue 1 (December 2017) - Lee, Jong-Uk; Chang, Hun; Lee, Hyeon; Jung, Chang; Bae, Da; Song, Hyun; Park, Jong; Uh, Soo-Taek; Kim, Young; Seo, Ki-Hyun; Park, Choon-Sik
Abstract Background Innate T helper type 2 (Th2) immune responses mediated by interleukin (IL)-33, thymic stromal lymphopoietin (TSLP), and IL-25 have been shown to play an important role in pulmonary fibrosis of animal models; however, their clinical implications remain poorly understood. Methods TSLP, IL-25, and IL-33 concentrations were measured in bronchoalveolar lavage fluids obtained from normal controls (NCs;n  = 40) and from patients with idiopathic pulmonary fibrosis (IPF;n  = 100), non-specific interstitial pneumonia (NSIP;n  = 22), hypersensitivity pneumonitis (HP;n  = 20), and sarcoidosis (n  = 19). Results The TSLP and IL-33 levels were significantly higher in patients with IPF relative to the NCs (p  = 0.01 andp  = 0.0001, respectively), NSIP (p  = 4.95E − 7 andp  = 0.0002, respectively), HP (p  = 0.00003 andp  = 0.000005, respectively), and sarcoidosis groups (p  = 0.003 andp  = 0.0001, respectively). However, the IL-25 levels were not significantly different between NC and IPF group (p  = 0.432). Receiver operating characteristic curves of the TSLP and IL-33 levels revealed clear differences between the IPF and NC groups (AUC = 0.655 and 0.706, respectively), as well as between the IPF and the other lung disease groups (AUC = 0.786 and 0.781, respectively). Cut-off values of 3.52 pg/μg TSLP and 3.77 pg/μg IL-33 were shown to differentiate between the IPF and NC groups with 99.2 and 94.3% accuracy. Cut-off values of 4.66 pg/μg TSLP and 2.52 pg/μg IL-33 possessed 99.4 and 93.2% accuracy for differentiating among the IPF and other interstitial lung disease groups. Conclusions Innate immune responses may be associated with the development of IPF. Furthermore, the IL-33 and TSLP levels in BAL fluids may be useful for differentiating IPF from other chronic interstitial lung diseases.